Screening, identification, metabolic pathway of di-n-butyl phthalate degrading Priestia megaterium P-7 isolated from long-term film mulched cotton field soil in Xinjiang - Yi, Yuanyang; Wang, Yuxian; Liu, Wanqin; Zhu, Jing; Gu, Meiying; Jia, Qiong; Li, Xue; Mutalifu, Munire; Jiang, Ling; Zhang, Wei; Zhang, Zhidong (Frontiers in Microbiology, 2025)
IntroductionDi-n-butyl phthalate (DBP) is one of the most widely used phthalate esters (PAEs) and is considered an emerging global pollutant. It may pose a significant threat to ecosystem and human health due to its residual hazards and accumulation in the environment. Bacteria-driven PAE biodegradation is considered an economical and effective strategy for remediating such polluted environments.MethodsA DBP-degrading bacterium (P-7), was isolated from long-term film mulched cotton field soil. Its identity was confirmed via physiological, biochemical, and 16S rRNA gene analyses. The degradation conditions were optimized through single-factor experiments and response surface methodology (RSM).Furthermore, the whole-genome sequencing coupled with metabolomics was employed to elucidate metabolic mechanisms.ResultsPriestia megaterium P-7 (P. megaterium P-7) achieved 100% DBP removal within 20 h under optimal conditions and exhibited broad substrate specificity for other PAEs. Genomic analysis identified key genes (lip, aes, ybfF, estA, and yvaK) encoding esterases/hydrolases that initiate DBP catabolism, converting it to phthalic acid (PA). Subsequent decarboxylation (pdc, bsdCD, mdcACDH, and lysA) and dioxygenase-mediated steps integrated PA into the TCA cycle. Metabolomics revealed three degradation pathways: decarboxylation (DBP → MBP → BB → BA→Catechol), hydrolysis (DBP → MBP → PA → PCA → Catechol) and direct β-oxidation (DBP → DEP → MEP → PA → Catechol).ConclusionP. megaterium P-7 demonstrates exceptional degradation efficiency, substrate versatility, and environmental stress tolerance, making it a promising candidate for bioremediation of organic pollutants in contaminated soil.